2021
DOI: 10.1136/bjsports-2020-103555
|View full text |Cite
|
Sign up to set email alerts
|

High rate of second ACL injury following ACL reconstruction in male professional footballers: an updated longitudinal analysis from 118 players in the UEFA Elite Club Injury Study

Abstract: BackgroundStudies on subsequent anterior cruciate ligament (ACL) ruptures and career length in male professional football players after ACL reconstruction (ACLR) are scarce.AimTo investigate the second ACL injury rate, potential predictors of second ACL injury and the career length after ACLR.Study designProspective cohort study.SettingMen’s professional football.Methods118 players with index ACL injury were tracked longitudinally for subsequent ACL injury and career length over 16.9 years. Multivariable Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 48 publications
5
52
1
4
Order By: Relevance
“…Despite the open debate on the use of targeted neuromuscular training [ 4 , 24 ], “at-risk” athletes were found to benefit more from additional customized programs focused on movement quality [ 20 ]. Given the growing incidence of ACL injuries in males and (recently) in females footballers [ 1 , 3 , 13 ], large-scale screenings and a broader awareness of the ACL injury risk are desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the open debate on the use of targeted neuromuscular training [ 4 , 24 ], “at-risk” athletes were found to benefit more from additional customized programs focused on movement quality [ 20 ]. Given the growing incidence of ACL injuries in males and (recently) in females footballers [ 1 , 3 , 13 ], large-scale screenings and a broader awareness of the ACL injury risk are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior cruciate ligament (ACL) injury risk reduction is a current open question for the sports medicine community. The investigation of situational patterns that lead to ACL injury has gained importance in the light of primary and secondary injury prevention [ 13 , 18 , 19 , 29 ]. Recent ACL injury video analysis studies [ 6 , 11 , 22 ] identified pressing/tackling as the most common situational patterns for ACL injury in football.…”
Section: Introductionmentioning
confidence: 99%
“…Schwer wiegt ebenfalls die Tatsache, dass bei 23–35 % der Sportler*innen innerhalb der ersten zwei Jahre nach einer VKB-Rekonstruktion das VKB erneut reißt. Im Profifußball wurde sogar eine Reverletzungsrate von 42 % innerhalb von 5 Jahren berichtet 9 . Beachtlich ist auch die Erkenntnis, dass ehemals verletzte Kniegelenke 7–14 Jahre nach VKB Rekonstruktion in 40–90 % der Fälle eine stärkere radiologische Arthrose zeigen als die kontralaterale Seite 40 .…”
unclassified
“…Der lange Rehabilitationszeitraum ist bei Patient*innen mit einer großen psychischen Belastung verbunden. Über die Rückkehrraten zum Wettkampfsport nach einer VKB-Reruptur ist wenig bekannt 9 .…”
unclassified
See 1 more Smart Citation